2022
DOI: 10.29166/ingenio.v5i2.4233
|View full text |Cite
|
Sign up to set email alerts
|

Non-Powered Hand Tool: Size Selection from an Anthropometric Ergonomic Point of View

Abstract: Abstrac In order to improve production companies are laying out resources to minimize time and save the worker force in each workstation. It means the ergonomist specialist must choose the correct hand device according to each worker. The goal of this research is to set forth an instructions set for tool hand tools selection focused on anthropometrics of the workers in order to rise production using the adequate tool for the task. During the study, the anthropometrical data is processed and evaluated to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The required tool for pinch grip submission must have a dimension ranging from 6.19 centimeters to 7.71 centimeters, according to the OSHA international standard, which suggests the values between these limits. The specified tool for activities requiring single-handle tools and power grip applications should be between 4.46 centimeters and a maximum size of 5.74 centimeters, and for activities involving double-handle tools, the recommended tool should be lower than 7.11 centimeters [46,47]. In this study, the researchers identified the correct ergonomic position for each task that involves hand tools to avoid wrong positions and reduce the possibility of injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The required tool for pinch grip submission must have a dimension ranging from 6.19 centimeters to 7.71 centimeters, according to the OSHA international standard, which suggests the values between these limits. The specified tool for activities requiring single-handle tools and power grip applications should be between 4.46 centimeters and a maximum size of 5.74 centimeters, and for activities involving double-handle tools, the recommended tool should be lower than 7.11 centimeters [46,47]. In this study, the researchers identified the correct ergonomic position for each task that involves hand tools to avoid wrong positions and reduce the possibility of injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The international bodies that set standards recommend that hand tools be measured solely in terms of task characteristics [48][49][50]. As a result, the processes required for making the right tool selection are described in this project.…”
Section: Discussionmentioning
confidence: 99%
“…Main risk factors to analyze in order to avoid ergonomic hazards into workplace.Work injuries can be caused by different factors and can be called accidents, but work-related illness can be classified and set into different types. The injuries are illustrated in Table 4[61].…”
mentioning
confidence: 99%